2019
DOI: 10.1590/s1677-5538.ibju.2018.0039
|View full text |Cite
|
Sign up to set email alerts
|

Salvage radiotherapy for biochemical recurrence after radical prostatectomy: does the outcome depend on the prostate cancer characteristics?

Abstract: Objective: To build a model to evaluate the impact of salvage radiotherapy (SRT) in men with PSA rise or persistent PSA after undergoing radical prostatectomy (RP). Materials and Methods: The study included 107 node-negative patients treated with SRT after RP at a single institution. Patients received SRT for either prostate-specific antigen (PSA) rising, or PSA persistence after RP. All patients received local radiation to the prostate / seminal vesicle bed. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Prostate cancer had important modifications in diagnosis, clinical management and surgical treatment in last years (8)(9)(10)(11). Multiparametric magnetic resonance imaging (mpMRI) has become the standard of care and provides useful information for prostate cancer diagnosis (12).…”
Section: Editorial In This Issuementioning
confidence: 99%
“…Prostate cancer had important modifications in diagnosis, clinical management and surgical treatment in last years (8)(9)(10)(11). Multiparametric magnetic resonance imaging (mpMRI) has become the standard of care and provides useful information for prostate cancer diagnosis (12).…”
Section: Editorial In This Issuementioning
confidence: 99%
“…Conventionally, early SRT has been defined as either intervention at shorter time interval following prostatectomy or as intervention at low initial PSA levels following biochemical relapse. Although multiple series have shown that initiation of SRT at lower PSA levels is associated with improved biochemical relapse‐free survival rates when compared to SRT given at higher PSA levels, less data have confirmed an impact upon more important clinical outcomes such as metastasis‐free or overall survival, thus contributing to uncertainty regard the optimal risk/benefit calculus when determining the timing of SRT 6–13 . Given the documented long natural history of prostate cancer even for patients with biochemical relapse after SRT, questions remain as to the value of early SRT while PSA remains at very low levels, versus initial expectant management followed by later salvage intervention at higher PSA levels.…”
Section: Introductionmentioning
confidence: 99%